The effect of covid-19 infection on the oral manifestations - Bahruddin Thalib; Alqarama M. Thalib; Nurlindah Hamrun; Nabilah A. Putri; Eshin UN. Rahman; Asmawati (Journal of Dentomaxillofacial Science, 2022)
Objective: This study was conducted to determine the effect of COVID-19 infection on the manifestations that arise in the oral environment. Methods : This study was conducted in the form of a literature review by collecting secondary data from online scientific article databases, such as PubMed, Google Scholar, and Science Direct. Results: There are various oral manifestations of COVID-19. The most common oral manifestations were xerostomia, impaired taste, burning sensation, and oral/dental pain. Conclusion : COVID-19 can cause manifestations in the oral environment which generally occur as early symptoms or in the acute phase of COVID-19.